Pengaruh Viskositas Cat Terhadap Sifat Keterbasahan Kayu Rajumas (Duabanga moluccana Blume): The Effect of Paint Viscosity on The Wettabillity of Rajumas Wood (Duabanga moluccana Blume) - Maulia, Zsarytha; Anwar, Hairil; Lestari, Andi Tri (PERENNIAL, 2023)
Rajumas wood is one of the local wood forest products from West Nusa Tenggara and has low strength and durability. Finishing treatment is needed for the service life of wood. One of the indicators of finishing quality is the ability of paint liquid wetting on the wood surface (wettability). This research aims to analyze the effect of paint viscosity on the wettability of rajumas wood. The samples used were radial and tangential sections in air-dry condition, and the wood surfaces were sanded with abrasive paper of 150 grit. The value of viscosities was 2.44, 2.41, and 2.32 poise from each percentage of paint and water ratio of 90%:10%, 80%:20%, and 70%:30%. Wettability was determined based on the rate of change equilibrium contact angle using the S/G equation. The research results show that the low viscosity value of Aqua Politur produces the lowest equilibrium value and highest wettability value (K-Value) in both radial and tangential sections. A high K-value indicates that Aqua Politur's ability to wet the wood surface is better, as shown by the paint percentage ratio of 70%:30%.